Existence of Classical Solution of a Quasilinear Stefan-Signorini Problem (Journal of Partial Differential Equations, 1991)
In this paper, we consider an one-phase quasilinear Stefan-Signorini problem. In [1] X. Liu has proved the existence and the uniqueness of this problem by the traditional penalty method (see [3] and [4]). Here we use the Mixed Scheme in [2] which is more suitable to the Stefan-Signorini problem and obtain more natural existence results.
Keywords: Quasilinear Stefan-Signorini problem; mixed scheme; priori estimates